(untitled) (Revista de História da UEG (REVHIST), 2019)
Abstract: This article discusses the concept of self-administration of sacred worship built by religious lay associations from the study of a case of exemplary punishment, involving the parish priest of Saint John of the King, the black brothers of the Rosary and the chaplain of the same confraternity in 1782 In this excerpt, we seek to identify the institution of chaplaincy as an instrument for attempting to establish limits of parish power. The particularist ideal of the sacred temple and the capacity for material and symbolic self-support of the sacred goods through chaplaincy were rhetorical arguments used by the brothers in defense of the autonomy of worship achieved during the establishment of lay religiousness in the urban mining centers. For the development of this analysis the royal correspondences of the brothers addressed to the Table of Conscience and Orders and the statutes and provisions of the Crown of confirmation of the commitments were used. Keywords: Chaplaincy. Brotherhood of the Rosary. Self-worship.